Effect of the Application Procedure on The Bond Strength of Universal Adhesive in Restoration Repair - Beyza Gül; Fatma Keçeci; Hüseyin Hatirli; Gülşah Tonga (Atatürk University, 2024)
Objective: This study aimed to evaluate the effect of reduced application time on the bond strength of a universal adhesive used for the repair of hybrid ceramic and composite resin restorations.Methods: In the study, a total of 48 rectangular prisms of sizes 7×6×2 mm hybrid ceramic (Vita Enamic, Zahnfabrik, Germany) and composite resin (Solare X, GC, Japan) specimens were prepared. All samples were aged with 5000 thermal cycles. Then, the upper surfaces of the samples were roughened with a diamond fissure bur (10-36µ, 852 FG Meisinger; Hager & Meisinger GmbH, Germany) with 5 strokes under water cooling. The samples were divided into 2 subgroups according to the different application times of the adhesive system (G-Premio Bond, GC, Japan) (n=12). Then, composite resin (Solare X, GC) was placed using plastic cylinder molds with 3 mm inner diameter and height and cured with light for 20 seconds. All samples were thermal aged and then a shear bond strength test was conducted. The data were analyzed with Two-way ANOVA and post-hoc Tukey HSD tests (p˂0,05).Results: Two-way ANOVA revealed that the repair bond strength of the 10 seconds of waiting was significantly higher than the quick application for both hybrid ceramic and composite resin (p˂0,05). It was determined that there was no significant difference between hybrid ceramic and composite resin in the both quick application group and 10 seconds waiting group (p˃0,05).Conclusion: Quick application procedure showed lower shear bond strength than 10 seconds waiting group for the repair of both composite resin and hybrid ceramic (p<0,05).Keywords:Quick application, Application time, Universal adhesive, restoration repair..